Začetna analiza stanja po izvedeni reorganizaciji - Rape, Tamara (Socialno delo, 2020)
The analysis is based on the Assembly (and following events) on the reorganisation of centres for social work that took place on 28 February 2019 and brought together practitioners, students and teachers of social work as a response to their distress caused by the reorganisation. The assembly has, in a comprehensive manner, debated the problem, seemingly of organisational nature, but it can have a fatal effect on the whole profession of social work and the social care sector, as well as an implication on the social work and management as sciences. Preliminary analysis of the effects of the reorganisation indicates to centralisation and bureaucratisation of the services, ineffectual rationalisation of the function of centres for social work, impairment of the professional autonomy, insufficient workforce and burnout. The assembly proposed civil monitoring mechanisms, demanded the decentralisation and relief from the overburdening administrative tasks and produced some practical and action effects in order to bring attention to the unsuitability of the present measures and to appeal for a constructive dialogue for improvement of the conditions and possibilities for better quality work in centres for social work.
Keywords: aktivistično raziskovanje; birokratizacija; bureaucratisation; civil monitoring; civilni monitoring; social affairs; social security; social workers; socialne zadeve; socialni delavci; socialno varstvo